Pengaruh Pemahaman Akuntansi, Sistem Informasi Akuntansi, dan Sistem Pengendalian Intern terhadap Kualitas Laporan Keuangan - Nur, Mawar Maulana; Sopanah, Ana; Puspitosarie, Endah (Magister Akuntansi Universitas Pancasila, 2023)
The purpose of this study is to test and analyze how the influence of accounting understanding, accounting information systems, and internal control systems on the quality of financial statements. This study used a quantitative approach with a causal type of research. The population in this study is the entire Regional Apparatus Work Unit (SKPD) within the Pasuruan City Government. The sample in this study used Financial Administration Officials (PPK) at the Pasuruan City Regional Government SKPD totaling 32 respondents from 32 SKPD using multiple linear regression analysis techniques and processed using the help of the IBM SPSS Statistics 25 computer application program. The output of this study is that the internal control system has a significant influence on the quality of financial statements, while partially the understanding of accounting and accounting information systems does not have a significant influence on the quality of financial statements. And simultaneously understanding accounting, accounting information systems, and internal control systems affect the quality of financial statements.